Sacred Violence - Jones, D. author. aut Link
VI, 270 p.
Keywords: Sacred Violence and Religious Violence examines the place that ideology or political religion plays in legitimizing violence to bring about a purer world. In particular, the book examines Islamism and the western secular, liberal democratic responses to it.